2011
DOI: 10.1007/s13105-011-0103-5
|View full text |Cite
|
Sign up to set email alerts
|

The hepatoprotective effect of coumarin and coumarin derivates on carbon tetrachloride-induced hepatic injury by antioxidative activities in rats

Abstract: Coumarins are a vast group of natural compounds and some of them possess antioxidant activities. The comparison of the antioxidant activity of some coumarins with various chemical molecular structure has not been investigated in previous studies. Therefore, this study was aimed to investigate the hepatoprotective effect against carbon tetrachloride (CCl(4)) -induced hepatic injury by coumarin (1,2-benzopyrone) and coumarin derivatives, esculetin (6,7-dihydroxycoumarin), scoparone (6,7-dimethoxycoumarin), and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 51 publications
(66 reference statements)
0
42
0
4
Order By: Relevance
“…1), scoparone is a main component in Artemisia capillaris and Artemisia iwayomogi, while scopoletin is strongly present in Artemisia iwayomogi (Seo et al, 2010). Both scoparone and scopoletin are known to have antioxidant activity (Thuong et al, 2010;Atmaca et al, 2011), and hepatoprotective effects (Kang et al, 1998;Murat Bilgin et al, 2011). Based on these publications, the two traditional hepatotherapeutic herbs seem to have hepatotherapeutic properties.…”
Section: Discussionmentioning
confidence: 99%
“…1), scoparone is a main component in Artemisia capillaris and Artemisia iwayomogi, while scopoletin is strongly present in Artemisia iwayomogi (Seo et al, 2010). Both scoparone and scopoletin are known to have antioxidant activity (Thuong et al, 2010;Atmaca et al, 2011), and hepatoprotective effects (Kang et al, 1998;Murat Bilgin et al, 2011). Based on these publications, the two traditional hepatotherapeutic herbs seem to have hepatotherapeutic properties.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that scopoletin contained A. iwayomogi is active in osteoporosis (Lee et al, 2013) and hepatic diseases (Atmaca et al, 2011) was reported. However, it was revealed in the present study that the five compounds, chlorogenic acid, 3,4-dicaffeoylquinic acid, rutin, patuletin 3-O-glucoside, and 2 00 -O-caffeoylrutin, are also potent peroxynitrite scavengers, in addition to scopolin and scopoletin, which are already known to be peroxynitrite scavengers from A. iwayomogi.…”
Section: Discussionmentioning
confidence: 98%
“…(Ahmad and Eram, 2011). Coumarins in C. murale have potent anti-oxidant effect and hence strong hepatoprotective activity (Amaca et al, 2011). …”
Section: Discussionmentioning
confidence: 99%